Nutrient Digestibility and Productivity of Bali Cattle Fed Fermented Hymenachne amplexiacalis Based Rations Supplemented with Leucaena leucocephala - . Riswandi; A. I. M. Ali; . Muhakka; Y. Syaifudin; I. Akbar (Media Peternakan, 2015)
An experiment was conducted to study the effects of lamtoro (Leucaena leucocephala) leaf supplementation in fermented kumpai grass (Hymenachne amplexiacalis) based rations on the productivity of Bali cattle. Variables measured were dry matter and organic matter intakes, nutrient digestibility (dry matter, organic matter, crude protein, and crude fiber), body weight gain, and feed efficiency. The types of rations were: Ration A= 45% fermented kumpai grass + 40% benggala grass + 15% concentrate + 0% lamtoro leaf, Ration B= 45% fermented kumpai grass + 30% benggala grass + 15% concentrate + 10% lamtoro leaf, Ration C= 45% fermented kumpai grass + 20% benggala grass + 15% concentrate + 20% lamtoro leaf, and Ration D= 45% fermented kumpai grass + 10% benggala grass + 15% concentrate + 30% lamtoro leaf. The supplementation of lamtoro leaf up to 30% into the ration could increase (P<0.05) dry matter and organic matter intakes, and crude protein digestibility. The highest body weight gain and feed efficiency were found in Bali cattle fed ration with 20% lamtoro leaf supplementation. The level of lamtoro leaf supplementation in the ration did not affect the digestibility of dry matter, organic matter, and crude fiber. It was concluded that the supplementation of lamtoro leaf in the ration could increase dry matter, organic matter, and crude protein intakes.  Addition of 20% lamtoro leaf gave the best effect on the increased body weight gain and feed efficiency in Bali cattle.Key words: Hymenachne amplexiacalis, Leucaena leucocephala, productivity, Bali cattle